Effects of Pile-driving Noise on the Behaviour of Marine Fish - Mueller-Blenkle, Christina; McGregor, Peter K.; Gill, Andrew B.; Andersson, Mathias H.; Metcalfe, Julian; Bendall, Victoria; Sigray, Peter; Wood, Daniel T.; Thomsen, Frank (Cranfield University, 2010)
Studies on the effects of offshore wind farm construction on marine life have so far focussed onbehavioural reactions in porpoises and seals. The effects on fish have only very recently come intothe focus of scientists, regulators and stakeholders. Pile-driving noise during construction is ofparticular concern as the very high sound pressure levels could potentially prevent fish from reachingbreeding or spawning sites, finding food, and acoustically locating mates. This could result in longtermeffects on reproduction and population parameters. Further, avoidance reactions might result indisplacement away from potential fishing grounds and lead to reduced catches. However, reactionthresholds and therefore the impacts of pile-driving on the behaviour of fish are completely unknown.We played back pile-driving noise to cod and sole held in two large (40 m) net pens located in a quietBay in West Scotland. Movements of the fish were analysed using a novel acoustic tracking system.Received sound pressure level and particle motion were measured during the experiments.There was a significant movement response to the pile-driving stimulus in both species at relativelylow received sound pressure levels (sole: 144 – 156 dB re 1μPa Peak; cod: 140 – 161 dB re 1 μPaPeak, particle motion between 6.51x10-3 and 8.62x10-4 m/s2 peak). Sole showed a significantincrease in swimming speed during the playback period compared to before and after playback. Codexhibited a similar reaction, yet results were not significant. Cod showed a significant freezingresponse at onset and cessation of playback. There were indications of directional movements awayfrom the sound source in both species. The results further showed a high variability in behaviouralreactions across individuals and a decrease of response with multiple exposures.This study is the first to document behavioural response of marine fish due to playbacks of pile-drivingsounds. The results indicate that a range of received sound pressure and particle motion levels willtrigger behavioural responses in sole and cod. The results further imply a relatively large zone ofbehavioural response to pile-driving sounds in marine fish. Yet, the exact nature and extent of thebehavioural response needs to be investigated further. Some of our results point toward habituationto the sound.The results of the study have important implications for regulatory advice and the implementation ofmitigation measures in the construction of offshore wind farms in the UK and elsewhere. First, theconcerns raised about the potential effects of pile-driving noise on fish were well founded. Thissuggests to both regulators and developers that the costs imposed by some mitigation measures thathave so far been applied following the precautionary principle go some of the way to addressing areal problem. We also suggest that our behavioural thresholds are considered in assessments ofimpacts of offshore wind farms in the UK and elsewhere. Mitigation measures should be furtherdiscussed developed and, if meaningful, applied especially if these could lead to a reduction ofacoustic energy that is emitted into the water column.Further studies should investigate the response at critical times (e.g. mating and spawning) and theeffects of pile-driving on communication behaviour. It will also be necessary to further investigatehabituation to the sound to effectively manage effects of pile-driving sound on marine fish.